Delivering Road Safety in Bangladesh : Leadership Priorities and Initiatives to 2030 - World Bank (World Bank, Washington, DC, 2020)
High fatality and injury rates on Bangladesh’s roads are undermining the remarkable progress that this South Asian nation has made on boosting economic growth and reducing poverty.